2003
DOI: 10.1002/jppr2003332114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Academic Detailing Within a Coordinated Care Trial

Abstract: Background: Academic detailing has been identified as an intervention that modifies health professionals' practice, particularly prescribing. Aim: To assess the impact of academic detailing on general practitioners' (GPs) prescribing for heart failure, and chronic pain associated with osteoarthritis, in an elderly population. Method: This was a quasi-experimental study embedded within a coordinated care trial, with a 12-month follow-up. 1151120 (96%) of GPs invited to participate received academic detailing vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Transparent evidence-based synthesis and presentation of a topic influences their views of the credibility and usefulness of an EV which can be tainted by perceptions of cost cutting 11 12 16 51 55–57. Programme designers should develop topic content and materials based on critical appraisal and systematic synthesis of evidence by clinicians (peers or experts), use of (local) data and identification of evidence-practice gaps,11 12 39 40 42 43 52 58–63 which also inform the design of support materials and preparation of the visitor 45 60. Providing clinicians with balanced information, acknowledgement of controversies and uncertainties in evidence contributes to transparency and conveys an understanding of greyness and complexity in clinical practice 2 12 38 48 52 53 56.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transparent evidence-based synthesis and presentation of a topic influences their views of the credibility and usefulness of an EV which can be tainted by perceptions of cost cutting 11 12 16 51 55–57. Programme designers should develop topic content and materials based on critical appraisal and systematic synthesis of evidence by clinicians (peers or experts), use of (local) data and identification of evidence-practice gaps,11 12 39 40 42 43 52 58–63 which also inform the design of support materials and preparation of the visitor 45 60. Providing clinicians with balanced information, acknowledgement of controversies and uncertainties in evidence contributes to transparency and conveys an understanding of greyness and complexity in clinical practice 2 12 38 48 52 53 56.…”
Section: Resultsmentioning
confidence: 99%
“…Rapport and relationships have to be built throughout a visit and over time with regular repeat visits and continuity of the visitor 12 40 44 52 55 63. Visitors and clinicians find that building or established relationships enhance the interaction and educational exchange and increase the trust between them 55 62 75…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows that educational outreach has been used in a variety of healthcare settings to change professional practice. [11][12][13][14][15][16] An updated Cochrane review, which included 69 studies involving more than 15 000 health professionals, assessed the effect of educational outreach on health professional practice or patient outcomes. The authors concluded that educational outreach alone, or when combined with other interventions, had a relatively small but consistent positive effect on prescribing behaviour, but for other types of professional practice, such as providing screening tests, educational outreach provided small to moderate changes in practice, although the effects were varied.…”
Section: Educational Outreachmentioning
confidence: 99%
“…The literature shows that educational outreach has been used in a variety of healthcare settings to change professional practice . An updated Cochrane review, which included 69 studies involving more than 15 000 health professionals, assessed the effect of educational outreach on health professional practice or patient outcomes.…”
Section: Introductionmentioning
confidence: 99%